2022
DOI: 10.21203/rs.3.rs-1975355/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reduction of phenolics in faba bean meal using recombinantly produced and purified Bacillus ligniniphilus catechol 2,3-dioxygenase

Abstract: Pulse meal should be a valuable product in the animal feed industry based on its strong nutritional and protein profiles. However, pulse meal contains anti-nutritional and anti-palatability compounds, including (poly)phenolics (tannic and non-tannic), such that improvements in pulse meal processing are still needed to increase its uptake by the industry. Microbial fermentation is currently used as a strategy to decrease tannin content, but results in the undesirable accumulation of monophenolics. Here we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Recently, our laboratory has identified a novel catechol 2,3 dioxygenase (C23O) from Bacillus ligniniphilus sp. L1 (BLC23O), which is a Mn 2+ -dependent EDO that has high substrate affinity for alkylated catechols (3-methylcatechol/3-ethylcatechol) in sodium phosphate buffer. , In comparing BLC23O activities with other EDOs, particularly the other Mn 2+ -dependent EDOs, we have found that different buffers were used for the kinetic assays: 50 mM Tris-HCl (pH 7.5) was used for Mn 2+ -dependent EDO from Bacillus sp. JF8, KP i buffer (pH 8.0) containing 0.75 mM 3,4-DHPA was used for Mn 2+ -dependent EDO from Arthrobacter globiformis CM-2, and potassium phosphate buffer (pH 7.5) was used for Mn 2+ -dependent EDO from Brevibacillus brevis .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our laboratory has identified a novel catechol 2,3 dioxygenase (C23O) from Bacillus ligniniphilus sp. L1 (BLC23O), which is a Mn 2+ -dependent EDO that has high substrate affinity for alkylated catechols (3-methylcatechol/3-ethylcatechol) in sodium phosphate buffer. , In comparing BLC23O activities with other EDOs, particularly the other Mn 2+ -dependent EDOs, we have found that different buffers were used for the kinetic assays: 50 mM Tris-HCl (pH 7.5) was used for Mn 2+ -dependent EDO from Bacillus sp. JF8, KP i buffer (pH 8.0) containing 0.75 mM 3,4-DHPA was used for Mn 2+ -dependent EDO from Arthrobacter globiformis CM-2, and potassium phosphate buffer (pH 7.5) was used for Mn 2+ -dependent EDO from Brevibacillus brevis .…”
Section: Introductionmentioning
confidence: 99%